Analisis Kesulitan Membaca Permulaan pada Siswa Kelas Rendah: Systematic Literature Review - Bersky, Amanda Berlia; Alwi, Nur Azmi (Lembaga Yasin AlSys, 2024)
One important component in the world of education is the ability to read. Even though Indonesia's population is increasing, interest in reading tends to decrease, as evidenced by the percentage of illiterates, which will reach 3.18% in 2023. Reading is the main capital for progress in education, starting from an early age with initial reading in elementary school. However, several difficulties, such as difficulty pronouncing letters, reading diphthongs, and spelling difficulties, are often experienced by students. The aim of this research is to examine the initial reading difficulties of lower-grade students and the strategies implemented by teachers to overcome these problems. This research is useful in helping students master the shapes of letters, words, and sentences, as well as increasing their activity in class. Apart from that, this research aims to increase teacher creativity in creating interesting learning and providing input to improve Indonesian language learning outcomes in lower grades. This research follows PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines using the Dimensions and Google Scholar databases.